Promotion of quality standard of herbal medicine by constituent removing and adding - Yan, Dan (Nature Publishing Group, 2014)
To identify major active constituents and measure their levels in a typical medicinal herb–Rhizoma coptidis, we applied the concept of removing and adding, taking inspiration from functional genetic methods. As this herb has bacteriostatic properties and is used to treat bacterial diarrhea, we examined the effects of individual constituents (berberine, palmatine, coptisine, epiberberine, jateorrhizine and columbamine) on the growth of Shigella dysenteriae with microcalorimetry. The removing and adding procedures revealed that berberine and coptisine were the main antibacterial constituents of R. coptidis, with bacteriostatic activities of 54.10% and 39.75%, respectively. The relative levels of berberine and coptisine in R. coptidis were 8.08%–31.92% and 4.05%–14.45%, respectively. On the basis of whole effect, the method of constituents removing and adding, coupled with a bioassay, is a useful strategy to identify the active constituents and measure their levels in herbal medicines, which may provide reference to other natural products.